Preparation and characterization of activated carbons from different kinds of coal - Damdin, Batkhishig; Barnasan, Purevsuren; Lin, Chung-Jun; Sanjaa, Batbileg; Alyeksandr, Ariunaa (Proceedings of the Mongolian Academy of Sciences, 2020)
Initial coal was purified in heavy liquid with a density 1.3 cm3 of ZnCl2 solution and purified coal was carbonized and the initial coal samples of each deposits were purified by pyrolysis. Thus, the yield of pyrolysis hard residue in the enriched sample was slightly higher than in the hard residue of initial coal. Therefore, pyrolysis hard residue of purified coal (carbonized sample) was activated at 800°C for 2 hours by preheated water steam. Activated carbons (ACs) and non-activated and non-carbonized coal from Baganuur, Ereen and Nariin Sukhait deposits were technically analyzed and their iodine number, BET surface area, pore volume and adsorption of methylene blue (MB) were determined. When these results were compared, these indicators increased 5-17 times in the Baganuur activated carbon (BN-AC), Ereen activated carbon (E-AC) and Nariin Sukhait activated carbon (NS-AC) as compared to inactivated coal.